Respostas
respondido por:
4
Olá boa noite!
6x - 10 = 26
6x = 26 + 10
6x = 36
x = 36/6
x = 6 {raiz}.
****Bons Estudos********
6x - 10 = 26
6x = 26 + 10
6x = 36
x = 36/6
x = 6 {raiz}.
****Bons Estudos********
Amanda15555565:
muito obrigado me ajudou muito ❤
respondido por:
2
Olá!!!
Vamos ver se é :
6x - 10 = 26
6x = 26 + 10
6x = 36
x = 36 / 6
x = 6
S = { 6 }
Espero ter ajudado....
Vamos ver se é :
6x - 10 = 26
6x = 26 + 10
6x = 36
x = 36 / 6
x = 6
S = { 6 }
Espero ter ajudado....
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás